The Oxford Handbook of Positive Psychology 2009
DOI: 10.1093/oxfordhb/9780195187243.013.0020
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Self-Esteem

Abstract: Self-esteem is examined here as an object of cultural discourse and as a socially constructed emotion grounded in mood. Scientific and popular conceptions of self-esteem share an emphasis on the person's acceptance by self and others, the evaluation of performance, social comparison, and the efficacy of individual action as the important roots of self-esteem. The present analysis deconstructs these elements, treating them not as psychological universals but rather as deeply rooted in the competing themes of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 0 publications
0
71
0
13
Order By: Relevance
“…There is also a smaller significant increase in self-efficacy, which is important given that Bandura (1997) reported that high self-efficacy significantly increases the likelihood of achieving success by influencing whether a task is attempted as well as the effort put into it and the persistence with which it is pursued in the face of difficulties or apparent lack of progress. A significant increase in self-esteem is also found post intervention, reflecting a feel good factor (Hewitt 2005). Increasing self-esteem in students is desirable given that previous research has established that high self-esteem is associated with greater educational attainment (Bachman and O'Malley 1977), task effort, and persistence (Felson 1984;McFarlin, Baumeister, and Blascovich 1984) and general coping ability (Taylor 1983).…”
Section: Post Educational Interventionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is also a smaller significant increase in self-efficacy, which is important given that Bandura (1997) reported that high self-efficacy significantly increases the likelihood of achieving success by influencing whether a task is attempted as well as the effort put into it and the persistence with which it is pursued in the face of difficulties or apparent lack of progress. A significant increase in self-esteem is also found post intervention, reflecting a feel good factor (Hewitt 2005). Increasing self-esteem in students is desirable given that previous research has established that high self-esteem is associated with greater educational attainment (Bachman and O'Malley 1977), task effort, and persistence (Felson 1984;McFarlin, Baumeister, and Blascovich 1984) and general coping ability (Taylor 1983).…”
Section: Post Educational Interventionmentioning
confidence: 96%
“…A self-esteem scale was included as the concept captures the individual's sense of self, of personal and social identity, and measures his/her feelings of self-worth or self-acceptance and self-confidence (Hewitt 2005). It is well established that high self-esteem is associated with greater educational attainment (Bachman and O'Malley 1977), task effort, and persistence (Felson 1984;McFarlin, Baumeister, and Blascovich 1984) and general coping ability (Taylor 1983).…”
Section: Measuring Students' Confidence In Their Ability To Learn Autmentioning
confidence: 99%
“…In real life, the feedback obtained by the individual from others during his/her interaction affects the self-esteem and while the positive feedback strengthens the self-esteem, negative ones make it go down. And the individual sometimes relies on maladaptive means to acceptance which is missing in this interaction (Hewitt, 2002). One of such maladaptive means can be stated as the overuse of Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the likes the users took for their shares on social networking sites allow them to feel better about themselves (Valkenburg, Peter & Schouten, 2006). The fact that 90% of the Internet users use a social networking site (Internet Society, 2012) and the positive feedback made by others strengthens the self-esteem (Hewitt, 2002) renders the relationship between the self-esteem and Internet use worhty of attention. It is no wrong to say that, with regards to self-esteem, similar situations apply to the gaming sites commonly used by Internet users.…”
Section: Self-esteem and Problematic Internet Usementioning
confidence: 99%
“…Self-esteem is rooted in an individual's acceptance, evaluation, and comparison of self, and is a sign of well-being (Hewitt 2005). It is an epiphenomenon that reflects how well one is doing in life (Seligman 1995).…”
Section: Self-enhancement Cognitive Biasmentioning
confidence: 99%